Features of genital herpes in women - E V Dvoriankova; L R Sakaniia; O R Babaev; V V Shakhzadov; I M Korsunskaia (IP Berlin A.V., 2018)
The paper presents a modern view of the current and the clinic of herpetic infection among women. The clinical manifestations and character of the course of atypical forms of herpes are described. The types of therapy of herpes simplex virus are considered and their own recommendations are given on the management of patients with recurrent genital herpes.